Faktor Risiko Yang Berhubungan Dengan Kejadian Kristal Batu Saluran Kemihdi Desa Mrisi Kecamatan Tanggungharjo Kabupaten Grobogan - Retno Sulistiyowati; Onny Setiani; Nurjazuli Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background: A stone in the urinary tract commonly known as Urinary Calculus has been recognized since the eraof Babylonia and Ancient Egypt. In 2002, Indonesia had 37,636 cases of Urinary Calculus. Male group has a 4times higher risk of Urinary Calculus than female group. In addition, it often happens at the age of 45 years. Morethan 80% of Urinary Calculus consists of calcium, i.e. calcium oxalate and calcium phosphate. The objective ofthis research was to analyze the risk factors of Urinary Calculus in urine among inhabitants.Method: It was an observational research using cross-sectional design. This research was conducted at Mrisivillage, Sub District of Tanggungharjo in Grobogan. Number of respondents was 45 persons. Furthermore,univariate, bivariate, and multivariate statistical techniques were applied to analyze data using SPSS version16.0.Result:This research showed that significant risk factors to the occurrence of Urinary Calculus were as follows:length of stay (p=0.028) and habit of vegetable consumption (RP=2.125; 95%CI: 1.078-4.187).Conclusion:People consuming high oxalate vegetables have a probability tosuffer from Urinary Calculus equalto 45.28%. They were recommended to drink as much as 2 – 2.5 liters/day, reduce consuming high oxalate foods,and consume various vegetables and fruits. In addition, they need to consume citrate if